Regenerative Translation of Human Blood-Vessel-Derived MSC Precursors - William C. W. Chen; Bruno Péault; Johnny Huard (Stem Cells International)
Mesenchymal stem/stromal cells (MSCs) represent a promising adult progenitor cell source for tissue repair and regeneration. Their mysterious identity in situ has gradually been unveiled by the accumulating evidence indicating an association between adult multipotent stem/progenitor cells and vascular/perivascular niches. Using immunohistochemistry and fluorescence-activated cell sorting, we and other groups have prospectively identified and purified subpopulations of multipotent precursor cells associated with the blood vessels within multiple human organs. The three precursor subsets, myogenic endothelial cells (MECs), pericytes (PCs), and adventitial cells (ACs), are located, respectively, in the three structural tiers of typical blood vessels: intima, media, and adventitia. MECs, PCs, and ACs have been extensively characterized in prior studies and are currently under investigation for their therapeutic potentials in preclinical animal models. In this review, we will briefly discuss the identification, isolation, and characterization of these human blood-vessel-derived stem cells (hBVSCs) and summarize the current status of regenerative applications of hBVSC subsets.